2001
DOI: 10.1051/lait:2001147
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the sensory characteristics, neutral volatile composition and gross composition of ten cheese varieties

Abstract: -Relationships between the odour, flavour and texture sensory attributes and the neutral volatile composition and gross composition of ten varieties of cheese were determined. Sensory evaluation was carried out by fifteen trained assessors who used a vocabulary of nine odour, twenty-one flavour and ten texture terms. Volatile compounds were isolated in a bench top purge and trap model system, trapped on Tenax-TA and analysed using gas chromatography coupled with mass spectrometry. Gross composition was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 28 publications
2
41
0
Order By: Relevance
“…This is because the concentration of esters is not always positively associated with fruitiness and can be correlated with other flavour attributes. For example, whereas esters are positively associated with the sweet odour of Swiss-type cheeses, esters are also positively correlated with acidic, peppery, salty and silage-like flavours in other cheese types (Lawlor et al, 2001). Also, the nutty flavour of Emmental cheese is found to be positively correlated with the concentration of ethyl acetate, whereas the sweet flavour of Dubliner cheese is negatively correlated with the concentration of ethyl hexanoate (Lawlor, Delahunty, Wilkinson, & Sheehan, 2002).…”
Section: Article In Pressmentioning
confidence: 93%
See 2 more Smart Citations
“…This is because the concentration of esters is not always positively associated with fruitiness and can be correlated with other flavour attributes. For example, whereas esters are positively associated with the sweet odour of Swiss-type cheeses, esters are also positively correlated with acidic, peppery, salty and silage-like flavours in other cheese types (Lawlor et al, 2001). Also, the nutty flavour of Emmental cheese is found to be positively correlated with the concentration of ethyl acetate, whereas the sweet flavour of Dubliner cheese is negatively correlated with the concentration of ethyl hexanoate (Lawlor, Delahunty, Wilkinson, & Sheehan, 2002).…”
Section: Article In Pressmentioning
confidence: 93%
“…Esters are positively associated with the sweet odour of Swiss-type cheeses (Lawlor, Delahunty, Wilkinson, & Sheehan, 2001). The unique esters in Swiss-type cheeses and their appearance in dairy fermentations where only propionibacteria are present (Liu, Holland, & Crow, unpublished data) indicate that the role of propionibacterial esterases/ lipases should be investigated further (see Section 5.6).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Hexanal originates from b-oxidation of unsaturated fatty acids, with the formation of an intermediate hydroperoxide (Engels, Dekker, De Jong, Neeter, & Visser, 1997). This aldehyde has been positively correlated with a caramel and creamy odour in a study carried out on ten European cheese varieties representing a range of flavour types (Lawlor, Delahunty, Wilkinson, & Sheehan, 2001). Levels of hexanal were higher in experimental cheese than in control cheese after 25 and 75 days of ripening (Table 1), in agreement with Garde et al (2002), who also found a higher level of hexanal in cheese made with a bacteriocin-producing adjunct culture after 75 days.…”
Section: Article In Pressmentioning
confidence: 99%
“…Esters are responsible for fruity flavours that can be considered as a flavour defect or contribute positively to cheese flavour [28]. In Swiss cheese, esters are though to contribute to the fruity note [33,34], and their presence has also been associated with the sweet odour of this cheese [27]. Numerous BC compounds were detected at a higher concentration in cheeses made using PAB than in the controls (Tab.…”
mentioning
confidence: 94%